The development and evaluation of modularized teacher's packages on techniques of using drosophila in high school biology - Samonte, Carolina Bautista (1978)
This study attempted to find out what specific topic of modularized instructional materials should be constructed for techniques in genetics for in-service training of biology teachers. The methodology involved three phases: 1. modification of some techniques in culturing, handling the Drosophila, and preparing the salivary gland chromosome; 2. specification of the objectives and problems; and 3. field testing of the modules to 20 highschool biology teachers of Ilocos Norte. Results of the data gathered provide information on the effectiveness and workability of the modules.